Recombination-Based In Vivo Expression Technology Identifies Helicobacter pylori Genes Important for Host Colonization - Castillo, Andrea R. (American Society for Microbiology (ASM), 2008)
Here we undertook to identify colonization and gastric disease-promoting factors of the human gastric pathogen Helicobacter pylori as genes that were induced in response to the stomach environment. Using recombination-based in vivo expression technology (RIVET), we identified six promoters induced in the host compared to laboratory conditions. Three of these promoters, designated Pivi10, Pivi66, and Pivi77, regulate genes that H. pylori may use to interact with other microbes or the host. Pivi10 likely regulates the mobA, mobB, and mobD genes, which have potential roles in horizontal gene transfer through plasmid mobilization. Pivi66 occurs in the cytotoxin-associated gene pathogenicity island, a genomic region known to be associated with more severe disease outcomes, and likely regulates cagZ, virB11, and virD4. Pivi77 likely regulates HP0289, an uncharacterized paralogue of the vacA cytotoxin gene. We assessed the roles of a subset of these genes in colonization by creating deletion mutants and analyzing them in single-strain and coinfection experiments. We found that a mobABD mutant was defective for murine host colonization and that a cagZ mutant outcompeted the wild-type strain in a coinfection analysis. Our work supports the conclusion that RIVET is a valuable tool for identifying H. pylori factors with roles in host colonization.